2015
DOI: 10.1590/s0034-8910.2015049006132
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed foods and the nutritional dietary profile in Brazil

Abstract: OBJECTIVE To assess the impact of consuming ultra-processed foods on the nutritional dietary profile in Brazil.METHODS Cross-sectional study conducted with data from the module on individual food consumption from the 2008-2009 Pesquisa de Orçamentos Familiares (POF – Brazilian Family Budgets Survey). The sample, which represented the section of the Brazilian population aged 10 years or over, involved 32,898 individuals. Food consumption was evaluated by two 24-hour food records. The consumed food items were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
330
9
79

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(486 citation statements)
references
References 22 publications
26
330
9
79
Order By: Relevance
“…These reasons are specified and discussed elsewhere (27,28,(47)(48)(49)(50)(51) . Ultra-processed products, produced and consumed in the amounts now characteristic in modern industrialized countries and settings, also have damaging impacts on culture, social life, local economies and the environment, as seen below.…”
Section: Boxmentioning
confidence: 99%
“…These reasons are specified and discussed elsewhere (27,28,(47)(48)(49)(50)(51) . Ultra-processed products, produced and consumed in the amounts now characteristic in modern industrialized countries and settings, also have damaging impacts on culture, social life, local economies and the environment, as seen below.…”
Section: Boxmentioning
confidence: 99%
“…Also, Bendino et al (2012) and Louzada et al (2015) report that over 40% of various cancers occur because of inadequate diets rich in food additives.…”
Section: Cytotoxic and Genotoxic Potential Of Powdered Juicesmentioning
confidence: 99%
“…Two studies observed a high contribution of ultra-processed food products to total caloric intake of children in the south of Brazil 19,20 . One of those studies used a convenience sample of 204 children aged 2 to 10 years, among whom the average daily energy intake from these food products was 47% 19 .…”
Section: Introductionmentioning
confidence: 99%